Pregnancy Outcome of Cervical Cerclage for Divergent Reasons in Dhofar Region, Oman - Veena Paliwal; Prabha Sinha; Shabnum Sibtain; Salochina Manjan; Ambia Ahmed; Tasabih Ali; Widad Yosuf (ziauddin University, 2024)
Background: Cervical insufficiency is one of the causes of preterm birth. The object of the study was to compare maternal and neonatal outcomes with different cerclage indications in Dhofar region, Oman.   Methods: It is a retrospective observational study. Data was collected from the electronic medical records system on standardized Performa in an Excel sheet. All cases of singleton pregnancy that underwent cervical cerclage were studied for the duration of 1/1/2018 - 30/4/2020 (28 months) at Sultan Qaboos Hospital, Salalah, Oman. Statistical analysis was done on SPSS-24.  P-value ≤ 0.05 was considered statistically significant. Results: We had 86 cases with cerclage included in the study, eight of which were lost from follow-up, therefore, analysis of 78 cases was done. Out of 78 cases, 61 were history indicated, 12 were ultrasound indicated and 5 were rescue cerclages. The 3 women had a bicornuate uterus. Maternal age and BMI were comparable in all groups.15 (19%) delivered before 32weeks, 151(19%) cases at 33-36weeks and 48(61.5%) at 37 weeks and more results were not significant in < 32 weeks group. The mode of delivery was vaginal 52(66.7%) and 21(27%) had cesarean section There were five miscarriages, 2 intrauterine fetal deaths (IUFD), and 4 early neonatal deaths (ENND). There were 5 cases of preterm premature rupture of membranes (PPROM), two abruptions and 2 cases had chorioamnionitis with septic shock. Cerclage to delivery interval in most cases was >20 weeks (3-26 weeks). Neonatal survival was comparable in history-indicated and ultrasound-indicated groups 87% and 91.7% respectively. 8 (10%) cases were admitted to the special care baby unit (SCBU) out of which 4 had early neonatal death due to extreme prematurity. Conclusion: The length of the cervix is reciprocally related to the risk of premature delivery. Therefore, the diagnosis and management of a short cervix is a substantial challenge in obstetrics.  Ultrasound-indicated had almost similar outcomes as history indicated. Rescue cerclage is worth attempting to improve fetal outcomes. Keywords: Cervical cerclage, cervical insufficiency, Preterm delivery, Second Trimester Miscarriages, Neonatal survival.